Somatometric characteristics of young males based on longitudinal observations of athletes - Diduch, Maria (Anthropological Review, 1984)
The paper analyses influence of a particular sport upon selected morphological characteristics of 88 young males observed longitudinally from 17 up to 24 years of age. Males specializing. in boxing and wrestling were compared with volleyball and basketball players. Significant differences in body dimensions were found between these two groups. These differences are attributable: to selection of youths for various sports, since there are no differences in the rate of growth of males practicing various sport disciplines as well as between athletes and non-athletes.